(untitled) - Jones, Frank A (Boston, Massachusetts, 1989)
This book helps provide a realistic approach to problems of school discipline. It contains a full range of philosophical and psychological approaches to classroom management and discipline, as well as dozens of activities designed to provide try-out experiences with the approaches.
Keywords: Classroom management,School discipline